SEMANGAT WIRAUSAHA: PERAN PENGETAHUAN WIRAUSAHA DAN MOTIVASI - Azwar, Azwar; Sitorus, Siti Hazar; Nesneri, Yessi (Jurnal Industri Kreatif dan Kewirausahaan, 2024)
Entrepreneurship is an important sector in advancing a country's economy. This research was conducted to see the influence of entrepreneurial knowledge and entrepreneurial motivation on the entrepreneurial spirit of UIN Suska Riau students. This research applied quantitative descriptive methods with data processing using the SPSS program. The research results showed that entrepreneurial knowledge had a positive and significant influence on students' business enthusiasm, motivation also had a positive and significant influence on students' business enthusiasm. Entrepreneurial knowledge and business motivation simultaneously have a positive and significant influence on the business enthusiasm of UIN Suska Riau students. The suggestion in this research is the need to increase students' entrepreneurial spirit by increasing entrepreneurial knowledge and entrepreneurial motivation.